A TVA–Single-Chain Antibody Fusion Protein Mediates Specific Targeting of a Subgroup A Avian Leukosis Virus Vector to Cells Expressing a Tumor-Specific Form of Epidermal Growth Factor Receptor - Snitkovsky, Sophie (American Society for Microbiology, 2000)
We have previously described an approach that employs retroviral receptor-ligand bridge proteins to target retroviral vectors to specific cell types. To determine whether targeted retroviral entry can also be achieved using a retroviral receptor–single-chain antibody bridge protein, the TVA-MR1 fusion protein was generated. TVA-MR1 is comprised of the extracellular domain of the TVA receptor for subgroup A avian leukosis viruses (ALV-A), fused to the MR1 single-chain antibody that binds specifically to EGFRvIII, a tumor-specific form of the epidermal growth factor receptor. We show that TVA-MR1 binds specifically to a murine version of EGFRvIII and promotes ALV-A entry selectively into cells that express this cell surface marker. These studies demonstrate that it is possible to target retroviral vectors to specific cell types through the use of a retroviral receptor–single-chain antibody fusion protein.